Evaluation of antibacterial agents to improve growth rate and efficiency of weaned pigs - G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
Pigs medicated 5 weeks with TNA-290 and ASP-250 had statistically greater (P<.05) average daily gains and those medicated with ASP-250 had significantly (P<.05) lower feed conversion rations than non-medicated pigs. Feed efficiency, feed consumption, or average daily gain among pigs medicated with Furox, ASP-250, or TNA-290 did not differ significantly.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Antibacterial agent; Growth rate; Efficiency